A Comparative and Analytical Study of the two Versions of Paṭhamasambodhi by His Holiness the Supreme Patriarch (Sā Pussadevo) - Padthapim, Phramaha Uthai; Tansrisook, Sompornnuch (Journal of Buddhist Studies Chulalongkorn University, 2024)
The Supreme Patriarch (Sā Pussadevo) wrote two versions of Pathamasambodhi, i.e. preaching version and Dhammasombat version, in the reign of King Rama IV and V respectively. This article aims to compare and analyze the content of the 2 Pathamasambodhi works as well as analyze the causes or factors influencing the versions during the two periods. It is found that the two versions are rather the same. The preaching version is synoptic, while the Dhammasombat version is the detailed one. The explanations in the texts are different from that in the Pali commentary and the popular Pathamasambodhi work by Prince Patriarch Paramanuchitchinorot. This reflects the author’s empiricism and rationalism of those ages. To emphasize the human Buddha’s wisdom, the details on the Buddha’s characteristics, insights, and magics according to the Pali canon have been preserved, while the details on inhuman beings assisting the Buddha’s insight have still been dropped. This is clear in the Dhammasombat version, in which other details except for the Brahma’s invitation to Dhamma dissemination have been added in accordance with the storyline of Pali canon. It can be said that the Supreme Patriarch adhered to the original concept of human Buddha according to Vajiranana Bhikkhu, the establisher of Dhammayuttika sect, even though the King Rama V promoted religious books following the Pali canon.